Structural and functional analysis of Oceanobacillus iheyensis macrodomain reveals a network of waters involved in substrate binding and catalysis. Issue 4 (26th April 2017) - Zapata-Pérez, Rubén; Gil-Ortiz, Fernando; Martínez-Moñino, Ana Belén; García-Saura, Antonio Ginés; Juanhuix, Jordi; Sánchez-Ferrer, Álvaro
Abstract : Abstract : Macrodomains are ubiquitous conserved domains that bind or transform ADP-ribose (ADPr) metabolites. In humans, they are involved in transcription, X-chromosome inactivation, neurodegeneration and modulating PARP1 signalling, making them potential targets for therapeutic agents. Unfortunately, some aspects related to the substrate binding and catalysis of MacroD-like macrodomains still remain unclear, since mutation of the proposed catalytic aspartate does not completely abolish enzyme activity. Here, we present a functional and structural characterization of a macrodomain from the extremely halotolerant and alkaliphilic bacterium Oceanobacillus iheyensis (OiMacroD), related to hMacroD1/hMacroD2, shedding light on substrate binding and catalysis. The crystal structures of D40A, N30A and G37V mutants, and those with MES, ADPr and ADP bound, allowed us to identify five fixed water molecules that play a significant role in substrate binding. Closure of the β6–α4 loop is revealed as essential not only for pyrophosphate recognition, but also for distal ribose orientation. In addition, a novel structural role for residue D40 is identified. Furthermore, it is revealed that OiMacroD not only catalyses the hydrolysis of O -acetyl-ADP-ribose but also reverses protein mono-ADP-ribosylation. Finally, mutant G37V supports the participation of a substrate-coordinated water molecule in catalysis that helps to select the proper substrate conformation.